2014
DOI: 10.1007/s10750-014-1849-x
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of sediment reworking by the Asiatic clam Corbicula fluminea Müller, 1774

Abstract: Active organisms modify the substratum in which they dwell. This process, called ''bioturbation'', affects the way that biogeochemical fluxes are mediated at the substratum-water interface. In the frame of this work, the bioturbation potential of the Asiatic clam Corbicula fluminea was characterized and quantified. We measured the displacement of fluorescent particles by C. fluminea burying in a sizebased experimental design in order to explore the effects of body-size on sediment reworking. Our results stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…Dreissena polymorpha and D. bugensis (Summers et al 1996), and Soletellina diphos (Taware et al 2012). Majdi et al (2014) also observed that small C. fluminea showed the highest net sediment-reworking rate. Mane (1975) stated that body size was an important factor to change the metabolic rate in bivalves; hence, the older and large individuals had a lower metabolic rate than small individuals.…”
Section: Discussionmentioning
confidence: 90%
“…Dreissena polymorpha and D. bugensis (Summers et al 1996), and Soletellina diphos (Taware et al 2012). Majdi et al (2014) also observed that small C. fluminea showed the highest net sediment-reworking rate. Mane (1975) stated that body size was an important factor to change the metabolic rate in bivalves; hence, the older and large individuals had a lower metabolic rate than small individuals.…”
Section: Discussionmentioning
confidence: 90%
“…Many marine species rework sediment and thus play a key role in benthic ecosystems by shaping local geochemical gradients and resource distribution (e.g., Aller, 1982;Solan et al, 2004;Meysman et al, 2006). By contrast, in freshwaters, the bioturbation ability of only a few species or taxonomic groups, including tubificids, chironomids, and clams, has been investigated (Fisher et al, 1980;Matisoff & Xiaosong, 1998;Ciutat et al, 2005;Stief & de Beer, 2006;Lagauzère et al, 2009;Mermillod-Blondin et al, 2013;Majdi et al, 2014a). Yet, the recent work of De Nadaï- Monoury et al (2013Monoury et al ( , 2014 has provided a wider overview of bioturbator diversity in freshwater ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…The proportions of microspheres were quantified by fluorescence (bottom reading fluorescence; k excitation = 441 nm; k emission = 486 nm; number of readings per well: 9 9 9) using a microplate reader Sinergy Mx (BioTek Instruments Inc., Winooski, VT, USA) following Lagauzere et al (2011) and Majdi et al (2014). Fluorescence values resulting from the microsphere emissions were obtained by subtracting the fluorescence value of natural sediments at different depths (additional cores) from the fluorescence measurements of incubated sediments.…”
Section: Sediment Reworking Quantificationmentioning
confidence: 99%
“…In spite of their large size, gallery-diffusors in the young mangroves induced lower biodiffusion rates than in the bare sediment. The larger surface area of organisms in young mangroves may create higher friction constraints within sediments, thus increasing the energetic cost and frequency of burrowing and decreasing the local transport of sediments (Majdi et al, 2014). Such constraints may also be induced by the subsurface rhizome network in young mangroves, which may limit the biodiffusion processes (Suzuki et al, 2012;Bernard et al, 2014).…”
Section: Bioturbation Measurementmentioning
confidence: 99%
See 1 more Smart Citation